2006
DOI: 10.1136/bjo.2006.094607
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of dysthyroid optic neuropathy: a European Group on Graves' Orbitopathy (EUGOGO) survey

Abstract: Background: This study was performed to determine clinical features of dysthyroid optic neuropathy (DON) across Europe. Methods: Forty seven patients with DON presented to seven European centres during one year. Local protocols for thyroid status, ophthalmic examination and further investigation were used. Each eye was classified as having definite, equivocal, or no DON. Results: Graves' hyperthyroidism occurred in the majority; 20% had received radioiodine. Of 94 eyes, 55 had definite and 17 equivocal DON. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
223
3
21

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 273 publications
(266 citation statements)
references
References 16 publications
8
223
3
21
Order By: Relevance
“…In our study, although the subjective orbital apex CI detected DON with 80.6% sensitivity for scores 1 or 2, none of the 36 affected orbits presented grade 3 apical crowding. These findings are remarkably different from previous studies using the Nugent subjective score to detect DON, 1,3,9,15 probably due to differences in subjective criteria for defining and grading apical crowding. While it seems clear that the Nugent apical crowding score is useful to raise suspicion of the presence of DON, it does not provide a clear definition of the position along the orbit where the coronal plane is used to determine it, nor does it provide a clear differentiation between grades 1, 2, and 3.…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…In our study, although the subjective orbital apex CI detected DON with 80.6% sensitivity for scores 1 or 2, none of the 36 affected orbits presented grade 3 apical crowding. These findings are remarkably different from previous studies using the Nugent subjective score to detect DON, 1,3,9,15 probably due to differences in subjective criteria for defining and grading apical crowding. While it seems clear that the Nugent apical crowding score is useful to raise suspicion of the presence of DON, it does not provide a clear definition of the position along the orbit where the coronal plane is used to determine it, nor does it provide a clear differentiation between grades 1, 2, and 3.…”
Section: Discussioncontrasting
confidence: 56%
“…16 A recent multicenter study found apical muscle crowding in 49 of 56 orbits with DON. 1 In another study, severe optic nerve crowding was retrospectively noted in 80% of orbits (16 of 20) with optic neuropathy compared with 29% of orbits without DON (10 of 34). No orbits with optic neuropathy scored lower than grade 2.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations